kappa-opioid receptor agonists modulate excitatory transmission in substantia gelatinosa neurons of the rat spinal cord - Randic, M (J Neurosci, 1995)
This study examined the effects of selective activation of kappa 1- opioid receptors on excitatory transmission in substantia gelatinosa (SG) using intracellular recordings from SG neurons in transverse slices of the young rat lumbar spinal cord. Monosynaptic and polysynaptic excitatory postsynaptic potentials (EPSPs) were evoked by orthodromic electrical stimulation of A delta or C primary afferent fibers in the dorsal root after blocking inhibitory inputs with bicuculline and strychnine, NMDA receptors with D-2-amino-5- phosphonovaleric acid and mu- and delta-opioid receptors with CTAP and ICI 174,864, respectively. Bath application of dynorphin A1-17 or U-69, 593 caused dual modulation of the peak amplitude of presumed monosynaptic AMPA receptor-mediated EPSPs, decreasing synaptic potentials at nanomolar concentrations in a majority of SG cells examined (dynorphin, 63%; U-69,593, 91%), and increasing EPSPs at micromolar concentrations. Only the inhibitory action of dynorphin A1- 17 was consistently and completely blocked by norbinaltorphimine (nor- BNI). Since U-69,593 and nor-BNI are selective for the kappa 1-opioid receptors, the depression of EPSPs is likely to be mediated by the kappa1-opioid receptors. Under conditions of blockade of synaptic transmission with TTX and mu-and delta-opioid receptors, dynorphin A1- 17 and U-69,593 hyperpolarize most of SG neurons and decrease their membrane input resistance, the finding suggesting that direct interaction of kappa-agonists with a postsynaptic receptor is likely explanation for the inhibition of EPSPs. However, in some SG cells, the inhibition of EPSPs appears to be of presynaptic origin since dynorphin A1-17 and U-69,593 did depress the EPSPs in the absence of changes in passive membrane properties. Rp-cAMPS, a membrane permeant potent competitive inhibitor of cAMP-activated protein kinase, prevented the depressant effect of dynorphin A 1-17. This finding suggested a possibility that dynorphin A1-17, acting through a decrease in intracellular cyclic AMP levels, can reduce the synaptic responses of SG neurons. These results provide the first electrophysiological demonstration that the activation of kappa 1-opioid receptors inhibits AMPA receptor-mediated primary afferent neurotransmission in the substantia gelatinosa of the young rat spinal cord. This effect may mediate the ability of kappa-receptor agonists to produce antinociception.